Exit Interview Analysis At Pt. Semen Indonesia Logistics - Zainul Milakh, Muhammad; Amalina Rizqi, Maulidyah (Dinasti Publisher, 2024)
Human resources (HR) are important assets for an organization. HR includes the abilities, skills, knowledge, and capabilities that individuals or groups possess to achieve organizational goals. In management, human resources (HR) includes everyone who contributes to an organization's operations, from top management to operational employees. It is very important to understand HR as an asset that can improve a company's performance and competitiveness. According to research, inadequate career development, poor work-life balance, and unsupportive boss behavior are the main reasons employees leave the company. Exit Interviews are an important way to find out the feedback of outgoing employees and provide important insights into company policies and working conditions. This study investigates the exit interview process of PT Semen Indonesia Logistik to find out the methods used, the problems faced, and the advantages. The results of the analysis show that data from outbound interviews can help companies understand the reasons why employees leave the company and provide constructive suggestions for improvements that can be made to improve employee retention and company performance. Based on these findings, there are suggestions to improve the exit interview process and maximize its benefits for the company.